Numerical Simulation of Wind-Driven Rain Based on the Eulerian Model - Chen, Hongyu; Zhou, Bo (Frontiers in Earth Science, 2022)
The wind-driven rain model based on the Eulerian multiphase model is the most widely used and closest to engineering applications. In this study, a real-world case of wind-driven rain was simulated using a wind-driven rain solver based on the Eulerian multiphase model developed by OpenFOAM. Separation of flow was observed at the front edges of the top of the building in the numerical simulation results, and the separated flow lines reconnected in the middle region of the roof. This type of corner flow with separation produces an accelerated horizontal airflow and increases the catch ratio; hence, there is often a larger catch ratio at the windward facades near the roof. The simulation results show that the Eulerian model used in this study possesses adequate capability and accuracy for wind-driven rain simulation.